Clinical features of CDK4/6 inhibitor-related interstitial lung disease in patients with breast cancer: a case series study. (14th November 2022) - Funasaka, Chikako; Naito, Yoichi; Kusuhara, Shota; Nakao, Takehiro; Nakajima, Hiromichi; Kawamoto, Megumi; Baba, Kaede; Mamishin, Kanako; Kondoh, Chihiro; Harano, Kenichi; Matsubara, Nobuaki; Hosono, Ako; et al.
Abstract: Background: Cyclin-dependent kinase 4/6 (CDK4/6) inhibitors are the standard treatment for advanced hormone receptor-positive breast cancer. Although interstitial lung disease is a rare (1–3.3%) but serious adverse event associated with CDK4/6 inhibitors, the incidence of interstitial lung disease in Japanese patients in the real world and the risk factors of interstitial lung disease are not clear. Methods: We retrospectively investigated the incidence of interstitial lung disease in 224 patients with advanced breast cancer who received CDK4/6 inhibitors at our hospital between 31 January 2017 and 31 January 2021. The correlation of age (>50 vs ≤50 years), presence or absence of previous history of interstitial lung disease, lung metastasis, smoking history and chest radiation with the development of interstitial lung disease was evaluated. Results: In total, 177 cases received palbociclib, 39 cases received abemaciclib and 8 cases received both palbociclib and abemaciclib, constituting a palbociclib group ( n  = 185) and an abemaciclib group ( n  = 47). At a median observation period of 607 days, 8.0% (18/224) cases (13 definite and 5 probable cases) had interstitial lung disease; 6.5% (12/185) of palbociclib-treated and 13% (6/47) of abemaciclib-treated cases. The median time to interstitial lung disease onset was 178 (range, 14–750) days. There was no significant correlation between the background factors studied and the development of interstitial lung disease. Conclusion: The frequency of CDK4/6 inhibitor-induced interstitial lung disease was higher than that reported in clinical trials. We did not identify any risk factors for the development of interstitial lung disease in this study, and thus, larger studies that include patient predisposition are required. Abstract : The frequency of CDK4/6 inhibitor-induced ILD in clinical settings was higher than that reported in clinical trials. We did not identify any risk factors for the development of ILD in this study.